Social influence of COVID-19: An observational study on the social impact of post-COVID-19 lockdown on everyday life in Kerala from a community perspective - Joyal Alias Saji; Bichu P Babu; Shaliet Rose Sebastian (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: The current novel coronavirus pandemic started as a simple outbreak in December 2019 from Wuhan, China, and it has now become a global threat. The governments from most of the countries including India have already taken strict precautionary measures to reduce the coronavirus spread such as social distancing, closure of schools, colleges, airports, restaurants, shopping malls, and other places where the people might gather. An increase in the levels of anxiety, aggression, depression, forgetfulness, and hallucinations are possible psychological effects of isolation. Too little is understood of the social impact of the pandemic. AIM: To study the social impact of post-COVID-19 lockdown in Kerala from a community perspective. MATERIALS AND METHODS: This cross-sectional survey was conducted among 700 families (50 families from each district) from all the 14 districts of Kerala from during April-May 2020 using respondent-driven sampling. The data were analyzed and the categorical variables have been presented as percentages and proportions. RESULTS: Anxiety (44%) and fear (44.3%) were reported by many of the study participants. The survey also picked up an increase in the prevalence of domestic violence (13.7%) during the period. The most common social change brought about by the lockdown was an improvement in the hygiene practices among the study population. CONCLUSION: The present study highlights the positive social changes brought about as a result of the COVID-19 lockdown. Further studies need to be conducted on a larger scale to assess the psycho-behavioural impact of COVID-19 on the wider population.